Critical swimming speed obtained by the 200-400 meters model in young swimmers - Zacca, R.; Castro, F. (Biomechanics and Medicine in Swimming XI, 2010)
The aim of the study was to compare the critical swimming speed (CSS) obtained by the 200-400m (CSS10) vs 14 different combinations of CSS and vs 1500m velocity (V1500) in 11 young sprint swimmers (male) of national competitive level. CSS1 (50-100m) was the combination that most overestimated CSS10. The lowest error on the estimation of CSS was observed for the CSS3 (50-400m) (-0.5%) and CSS7 (100-400m) (0.8%). CSS10 overestimated V1500 by 3.5%. This might suggest studies to measure the level of agreement between CSS10 vs the other combinations and between CSS10 vs V1500 to check whether this level of agreement will be maintained until adulthood.